Compact phase comparison system for the synthetic HCOOH laser diagnostic system in HL-2A. (27th September 2022) - Zhang, W.; Wu, T.Y.; Li, Y.G.; Zhang, Y.P.
Abstract: Recently, a synthetic formic-acid laser diagnostic system has been deployed in HL-2A tokamak. However, the main electronics of the subsystems were discrete devices, and multimodal data analysis remained out of reach. In this work, we developed a novel compact high sensitivity Phasemeter (CHSP) system to integrate interferometer, far-forward collective scattering diagnostic (FCS), and Faraday effect polarimeter. It provides a framework for real-time intelligent diagnosis such as plasma disruptions prediction. We also propose a Synchronous Fast Fourier Transform (SFFT) method for suppression of spectral leakage and noise reduction. Experimental results indicate that the electronics system accuracy is about 1.0× 10 15 /m -3, which fully meets the requirements of HL-2A. This work represents a crucial step toward a high-performance intelligent diagnosis in HL-2A.